Muslim Women Stereotyped: Deconstructing Common Myths (American Journal of Islam and Society, 2014)
In this paper, I use global education theories and principles to deconstruct common myths regarding Muslim women and the Islamic treatment of women. This paper demonstrates how global education theory and principles can be used to deconstruct and reframe the myths and misconceptions perpetuated on Muslim women. The three major themes explored – female circumcision, polygamy, and subordination – are embedded in a single case and serve as a rich illustration of the usefulness of applying global education principles. They have been developed over the past thirty years to deconstruct and reframe western myths and misconceptions regarding Muslim women.